Establecimiento in vitro de tacaco [Sechium tacaco (Pittier) C. Jeffrey syn. Frantzia tacaco] - Murillo Quesada, Marcelo Efrén (2019)
UCR::Docencia::Ciencias Agroalimentarias::Facultad de Ciencias Agroalimentarias::Escuela de Agronomía